AKTIVITAS DAYA HAMBAT ISOLAT ACTINOMYCETES DENGAN LAMA FERMENTASI YANG BERBEDA TERHADAP PERTUMBUHAN KLEBSIELLA PNEUMONIAE - Annisa Nur Insani (2022)
Actinomycetes are filamentous, Gram positive bacteria widely distributed in soil and are able to produce secondary metabolites useful as antibiotics. The synthesis of secondary metabolites of Actinomycetes is influenced by the growth conditions of each isolate, including fermentation period. Klebsiella pneumoniae is a bacterial opportunistic pathogen causing lower respiratory tract infection. Currently, K. pneumoniae is gaining serious attention due to the increase in infection numbers and increase findings of bacterial resistance. This study aimed to determine the inhibition activity of Actinomycetes with different fermentation periods against the growth of K. pneumoniae. Actinomycetes were isolated from soil in Kebun Raya Bogor and grown on Starch Casein Agar (SCA) medium before being fermented in liquid media consisting of 2% of mannitol, 2% of pepton, and 1% of glucose with incubation time of 6,7, and 8 days. Antibacterial activity test was conducted on Mueller Hinton Agar (MHA) medium using well diffusion method. Actinomycetes after 6,7, and 8 days of fermentation were able to inhibit the growth of K. pneumoniae with an average inhibition zone of 4,46 mm; 4,94 mm; and 5,04 mm respectively. The antibacterial activity of Actinomycetes can occur through various mechanism, ranging from inhibition of cell wall synthesis to nucleic acid and protein synthesis. One Way ANOVA test showed that there were significant differences between the inhibition zone produced by each fermentation group. Actinomycetes posses antibacterial activity against the growth of K. pneumoniae with the highest activity achieved by Actinomycetes with fermentation time of 8 days.